The Effect of Triponyl Sulphate on Fetuses Development and Placental Abnormalities in Inducing Preeclampsia of Rattus norvegicus animal model - Purwatiningsih, Wawid; Aryani, Dhita Evi; Vidiastuti, Dian; Oktanella, Yudit; Firmawati, Aulia (Veterinary Biomedical and Clinical Journal, 2019)
Preeclampsia is one of the obstetrical problems that can cause maternal and fetal morbidity and mortality. Preeclampsia causes the fetus born prematurely and low fetal weight. This is caused by high blood pressure which causes decrease of blood delivery to the placenta, so the supply of oxygen and food to the fetus decreases. As a result, fetal development inhibits and trigger born prematurely. More fatal, this disease cause the release of placental tissue from the uterus prematurely. The aim of this study was to determine the effect of administration of triponyl sulfate as induction of increased blood pressure in preeclampsia animal models, fetal development with alizarin red staining and placental abnormalities. The experimental animals were rats Rattus norvegicus mated with male rats monomating , 4 months old and 250-300 grams body weigh. Pregnant female rats were induced by triponyl sulfate 70 mg / kg BW (k +) and without induced by triponyl sulfate (k-). The results of the study showed that there were formation of the sternal bone in k- and malformation of the sternum bone at k +. Placental abnormalities occured in k +, it could be seen in the presence of ghos villi in blood vessel abnormalities in the preeclampsia placenta caused by there was no invation of trophoblast cells in the whole or partial spiral arteries and the mean of blood pressure increased.